Clinical Outcomes and Prognostic Analysis of 101 Patients of Central Neurocytoma: A 10-Year Treatment Experience at a Single Institution - Xie, Qiongxuan; Xie, Bin; Ou, Ludi; Wang, Min; Tang, Ziqing; He, Yuxiang; Yang, Xiaoyu; Hong, Jidong; Lyu, Zhiping; Wei, Rui (Frontiers in Oncology, 2022)
Objective Central neurocytoma (CN) is a rare type of tumor that currently lacks an optimal treatment protocol. This study aimed to explore the clinical outcomes of CN in a cohort of 101 patients and identify prognostic factors associated with multiple treatment modalities. Methods This monocentric study retrospectively analyzed the clinical data of 101 CN patients who underwent surgical resection. The patients were followed up, and their overall survival (OS) and progression-free survival (PFS) were calculated. Results For the entire cohort, the 5- and 10-year OS rates were 88.7% and 82.8%, respectively, and the 5- and 10-year PFS rates were 86.5% and 64.9%, respectively. Of the 82 (81.19%) patients with CN who underwent gross total resection (GTR), 28 (28/82, 34.1%) also received radiotherapy (RT). Of the 19 (18.81%) patients with CN who underwent subtotal resection (STR), 11 (11/19, 57.9%) also received RT or stereotactic radiosurgery (SRS). Compared to STR, GTR significantly improved the 5-year OS (92.4% vs. 72.4%, P=0.011) and PFS (92.4% vs. 60.4%, P=0.009) rates. Radiotherapy did not affect OS in the GTR group (p=0.602), but it had a statistically significant effect on OS in the STR group (P<0.001). However, the OS (P=0.842) and PFS (P=0.915) in the STR plus radiotherapy group were comparable to those in the GTR alone group. Compared to STR alone, STR plus radiotherapy improved the 5-year PFS rate from 25% to 75% in patients with atypical CN (P=0.004). Cox regression models and a competing risk model showed that the removal degree and radiotherapy were independent prognostic factors for survival. With improvements in modern radiotherapy techniques, severe radiotherapy toxicity was not observed. Conclusion Our findings support the use of GTR whenever possible. Radiotherapy can improve the prognosis of patients who undergo STR, especially in atypical CNs having a higher tendency to relapse. Close imaging follow-up is necessary. Our findings will help clinicians to select optimal, individualized treatment strategies to improve OS and PFS for patients with CN.